Studies of Physicochemical, Microbiological and Sensory characteristics of Paneer (Indian Cottage Cheese) to check the efficacy of clove-oil nanoemulsion in enhancing its shelf-life - D Bhardwaj; Mann, B; Sharma, R; Kumar, R; Rashmi H.M; K Gandhi; Sukthija M.P.; Minaxi Sharma (Indian Journal of Dairy Science, 2024)
Paneer is a popular dairy product in India and is highly vulnerable to spoilage due to its high moisture and nutrient content. In the presented study paneer samples were treated with clove-oil nanoemulsion and its effectiveness in enhancing the shelf-life of paneer was studied by analyzing the physicochemical, microbiological and sensory characteristics of the stored samples. Paneer treated with clove-oil nanoemulsion showed the lesser significant increase (P